2017
DOI: 10.14207/ejsd.2017.v6n2p1
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Biodiversity in Climate Change Adaptation Planning

Abstract: Climate change is one of the biggest threats to food production worldwide. Recently, an increasing number of initiatives have embraced the concept of climate smart agriculture to respond to climate change adaptation and mitigation challenges. A central component of this approach is the use of agricultural biodiversity at the genetic, species and ecosystem levels for increasing productivity, adaptability and resilience of agricultural production systems. This paper analyses the extent to which the use of agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Increases in the frequency and intensity of extreme climatic events will amplify agricultural production risks, particularly among smallholder farmers in developing countries (Morton, 2017). In such scenario, it is essential to increase the biodiversity in the of agricultural systems at the genetic and ecosystem levels, to improve their resilience thereby reducing farmers' vulnerability to climate related risks (Jackson et al 2010;Villanueva et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the frequency and intensity of extreme climatic events will amplify agricultural production risks, particularly among smallholder farmers in developing countries (Morton, 2017). In such scenario, it is essential to increase the biodiversity in the of agricultural systems at the genetic and ecosystem levels, to improve their resilience thereby reducing farmers' vulnerability to climate related risks (Jackson et al 2010;Villanueva et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Climate change poses one of the biggest threats to food production worldwide (Villanueva et al, 2017). It is likely to adversely affect food security in many regions of the world (Dar and Gowda, 2013).…”
mentioning
confidence: 99%
“…Sultan et al (2013) predicted sorghum yield losses of up to 41% in West Africa, a major sorghum‐growing region in Africa, as a result of climate change. A central element of the sustainable agricultural development concept and the climate‐smart‐agriculture approach is the use of agricultural biodiversity at the genetic, species, and ecosystem levels for increasing productivity, adaptability, and resilience of agricultural production systems (Villanueva et al, 2017). Sorghum, which originated near the equator in northeastern Africa, is a short‐day crop and exhibits substantial sensitivity to both photoperiod and temperature (Miller, 1982).…”
mentioning
confidence: 99%
“…Evidence suggests, however, that concrete progress in this regard has been fairly limited. For example, a study of the 50 national adaptation programmes of action (NAPAs) developed by January 2015 (Villanueva, Halewood and Noriega, 2017) concluded that they do not effectively integrate agrobiodiversity, noting for example that although NAPAs often stress the importance of food security and nutrition, few target the improvement and use of local, indigenous or traditional crop varieties and animal breeds and none of those reviewed address underutilized species. The study also concluded that the NAPAs reviewed are overly compartmentalized at governmental level and that there is a lack of dialogue between ministries of agriculture and the environment on the protection and use of agrobiodiversity (ibid.).…”
Section: Climate Change Policy and Programmesmentioning
confidence: 99%